Ekaterina Sosnina, with the participation of Christian Pile. French in the Caucasus. Historical and picturesque journeys of XIII-XIX centuries. Creative workshop BLG, Yessentuki, 2015. 336 p - Sergei Dudarev (Гуманитарные и юридические исследования)
-